Lupus erythematosus cell phenomenon in synovial and peritoneal fluids in systemic lupus erythematosus: smoking guns, crime scenes and a twist. (26th December 2014) - Tay, Sen Hee; Nga, Min En; Koh, Dow‐Rhoon; Mak, Anselm
Abstract The presence of the lupus erythematosus (LE) phenomenon has been generally conceptualized as an in vitro occurrence where numerous damaged cells are present and substantial nucleo‐phagocytosis has occurred. In systemic lupus erythematosus (SLE), the positive LE cell phenomenon has been shown to indicate active disease with major organ involvement which potentially warrants prompt and heavy immunosuppressive therapy. We report a 36‐year‐old woman with a known history of SLE who presented with fever, left knee effusion, polyserositis, pancytopenia, low complement and high anti‐dsDNA antibody levels whose immunosuppressive treatment was escalated in view of the clinically and serologically active SLE, accompanied by the presence of LE cells in her inflammatory yet sterile left knee synovial fluid. Within 3 days of immunosuppressant escalation, her ascites worsened. While microscopic examination of the ascitic fluid also revealed LE cells, culture of the ascitic fluid later grew Candida parapsilosis. The patient subsequently responded to the addition of anti‐fungal therapy into her augmented immunosuppressive regime. Coexistence of the LE cell phenomenon and infection in SLE patients has hitherto not been described. This case illustrates that infection remains to be meticulously excluded despite the presence of the LE phenomenon in the context of clinically and serologically active SLE.